A Review on Schiff Bases Compounds: Synthesis, Application, and a Versatile Pharmacophore: A Review on Schiff Bases Compounds: Synthesis, Application, and a Versatile Pharmacophore - Taresh, Ban H. (Scientific Journal of Medical Research, 2022)
Hugo Schiff named Schiff bases, which are highly reactive chemical compounds widely employed Pigments and dyes, catalysts, organic synthesis intermediates, and polymer stabilizers are only some of the applications. Antimalarial, antibacterial, antifungal, antiinflammatory, and antiviral actions of Schiff bases have been reported in the literature. Schiff bases are also known for forming complexes with a large selection of metals. Schiff base complexes containing metals, as well as Schiff bases alone, have been discovered. Have frequently shown anticancer action. We will focus on the most notable examples of compounds in this class described in the literature.